A Limit Relation for Dunkl-Bessel Functions of Type A and B - Rösler, M.; Voit, M. (Symmetry, Integrability and Geometry: Methods and Applications, 2008)
We prove a limit relation for the Dunkl-Bessel function of type BN with multiplicity parameters k₁ on the roots ±ei and k₂ on ±ei±ej where k₁ tends to infinity and the arguments are suitably scaled. It gives a good approximation in terms of the Dunkl-type Bessel function of type An₋₁orresponding limit relation for Bessel functions on matrix cones.